Exploring powder blend uniformity of a binary mixture containing metformin HCl and HPMC by differential scanning calorimetry (DSC) - Hilmi, Nur Nadhirah; Husain, Nur Khairunnisa; Mahmood, Syed; Chatterjee, Bappaditya; Mandal, Uttam Kumar (2015)
V Blender, also known as twin–shell mixer, is widely used in pharmaceutical industries for mixing powders, granules, and other solid materials1-2. Its mixing mechanism involves continuous splitting, followed by intermixing of powder materials as the shell rotates on its horizontal axis. Powder mixing is considered a critical step in process scale up during pharmaceutical product development as well as routine commercial manufacturing3. However, the Pharmaceutical Industries heavily rely on chemical analysis of active drug present in the powder mixture by UV or HPLC for the same. The objective of this research work is to analyze mixing uniformity of a binary mixture containing HPMC and metformin HCl (95:5 w/w) at 50% and 60% occupancy of a laboratory scale V blender. The results of the DSC method were further confirmed by a UV method. Powder samples were withdrawn at 5 min, 10 min, 15 min, and 20 min intervals each of the top, middle, and bottom positions of the blender. Recovery of metformin HCl after 20 min of mixing by both the UV method (2.66±1.10% and 2.60±0.32% at 50% and 60% occupancy levels, respectively) and the DSC method (2.68±0.22% and 2.29±0.14% at 50% and 60% occupancy, respectively) were found to have similar trends. Also, maximum RSD of enthalpy (21.55 at 10 min at 50% occupancy) for sample analysis by the DSC method was comparable to that of the UV method (25.201 at 15 min at 50% occupancy). DSC method can be further explored as an alternative of UV spectroscopy or HPLC method to assess the mixing uniformity of powder samples in pharmaceutical industries.